Program Preventif Bunuh Diri Untuk Mengurangi Ide Dan Percobaan Bunuh Diri - Fitri, Arrumaisha (Universitas Darul Ulum, 2023)
The university students in six ASEAN Countries have 11,7% of suicidal ideation and 2,4% of suicide attempts. Suicidal ideation is a person’s thoughts to end his/her life, while attempted suicide is the behavior of self harm-with the intention to die. The reasons are hopelessness, depression, relationship break-up, lack of social support, financial crisis, and academic stress. Therefore, there are prevention programs to reduce the impact of these maladaptive thoughts and behaviors. This review aims to provide a comprehensive overview of how suicide prevention programs can give positive effects on reducing suicidal ideation and suicide attempt. Data were collected from five databases, which included Google Scholar, ResearchGate, Sciencedirect, JStore, and Emerald. This study synthesized the finding of 10 studies published from 2018 to 2022. The results reveal some suicide prevention programs to overcome suicide by reducing suicidal ideation and suicide attempts. The programs consist of university suicide prevention programs such as psychoeducation, training, and peer leadership; screening tools to know a student with a high risk of mental health problems connected with suicide; gatekeeping training for lecturers, university administrators, and counselors; curriculum evolved mental health; and peer to peer support programs. Furthermore, the involvement of the university is important to focus on the community, use technology, and make networking between educational institutions and mental health services. Assessment is needed to give data about students with a high risk of suicidal ideation and suicide attempt. The result of prevention programs reduce suicidal thoughts and behavior by understanding and giving social support to students.